Development of an Intelligent Catch the Stick System for Measuring Human Motor Coordination and Reaction Speed - Wirawan, Nanda Tommy; Ernes, Risa Nadia (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2026)
Conventional clinical methods for assessing sensorimotor coordination, such as the Fugl Meyer Assessment (FMA) and Action Research Arm Test (ARAT), often lack the objectivity and high-resolution sensitivity required to detect subtle micro improvements in motor performance. This study presents the design, development, and validation of an intelligent